Neither high-dose nor low-dose brachytherapy increases flap morbidity in salvage treatment of recurrent head and neck cancer - Henderson, Peter W.; Kutler, David I.; Parashar, Bhupesh; Otterburn, David M.; Cohen, Marc A.; Spector, Jason A. (Journal of contemporary brachytherapy, 2016)
While brachytherapy is often used concurrently with flap reconstruction following surgical ablation for head and neck cancer, it remains unclear whether it increases morbidity in the particularly high risk subset of patients undergoing salvage treatment for recurrent head and neck cancer (RH&NC). A retrospective chart review was undertaken that evaluated patients with RH&NC who underwent flap coverage after surgical re-resection and concomitant brachytherapy. The primary endpoint was flap viability, and the secondary endpoints were flap and recipient site complications. In the 23 subjects included in series, flap viability and skin graft take was 100%. Overall recipient site complication rate was 34.8%, high-dose radiation (HDR) group 50%, and low-dose radiation (LDR) group 29.4%. There was no statistically significant difference between these groups. In patients who undergo flap reconstruction and immediate postoperative radiotherapy following salvage procedures for RH&NC, flap coverage of defects in combination with brachytherapy remains a safe and effective means of providing stable soft tissue coverage.